APPROPRIATE IRRIGATION PROCEDURES AND CULTIVATION AGROTECHNOLOGY OF SOYA AND SUNBACKAR VARIETS PLANTED AS REPRODUCTIVE CROPS - Eshonkulov Jamoliddin Saporboy ugli, Kamilov Bakhtiyor Sultanovich, Shamsiyev Akmal Sadirdinovich, Nasirov Bakhtiyor Salakhiddinovich, Sheraliyev Khamidulla, Ziyatov Musulman Panjievich (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This article is part of the practical project MV-A-QX-2018-204 in the experimental fields of the Research Institute of Cotton Breeding, Seed Production and Agrotechnology, ie in the conditions of typical irrigated gray Tashkent and Kashkadarya region legumes (Orzu, Arleta). ), data on the timing of sowing, germination, growth, development of varieties of oilseed sunflower (Jahongir, Navruz), the optimal timing of irrigation to obtain high and quality grain products, irrigation procedures, development of irrigation standards and effective care agrotechnology.